Molecular identification and phylogenetic analysis of Papaver based on ITS2 barcoding. Issue 2 (1st November 2021) - Cheng, Liu; Lin, Ziqing; Xin, Cairui; Sun, Haolin; Li, Xinyu
Abstract: In forensic cases suspected to involve Papaver somniferum, species identification is key to the investigation. To accurately detect and identify P. somniferum as well as common adulterants of the same genus, 19 internal transcribed spacer 2 (ITS2) sequences of P .  somniferum (256 bp), Papaver canescens (254 bp), Papaver nudicaule (254 bp), Papaver pavoninum (250 bp), Papaver radicatum (254 bp), and Papaver rhoeas (256 bp) were obtained. Based on the ITS2 sequence, similarity analysis via BLAST, the nearest Kimura‐2‐parameter (K2P) genetic distances were calculated, and a phylogenetic tree was constructed using MEGA X software for the identification of six species of Papaver . Finally, differences in the ITS2 secondary structure between species were analyzed. The best matches of the P .  somniferum ITS2 sequence were of other P .  somniferum from different sources. The nearest K2P genetic distances between P .  somniferum and its counterparts from other sources were zero, which was the smallest pairwise genetic distance among distances from the other five Papaver species. Various sources of P .  somniferum clustered into an independent branch in the phylogenetic tree. The secondary structures of P .  somniferum and P. rhoeas were significantly different from those of the other four species of Papaver. In summary, P .  somniferum can be effectively distinguished from five closely related plants of the same genus by using ITS2 as a DNA barcode.